Social order and social justice: moral intuitions, systemic racism beliefs, and Americans’ divergent attitudes toward Black Lives Matter and police - Silver, Eric (Criminology, 2022)
We examine the influence of moral intuitions on Americans’ divergent attitudes toward Black Lives Matter (BLM) and police. Drawing on Moral Foundations Theory, we hypothesize that individualizing moral intuitions that put care and protection of the vulnerable at the center of moral concern (a social justice orientation) lead people to express positive feelings toward BLM and negative feelings toward police, whereas binding moral intuitions that put social stability at the center of moral concern (a social order orientation) lead people to express positive feelings toward police and negative feelings toward BLM. We find strong support for these hypotheses using data from a 2021 YouGov survey of 1,125 U.S. adults including a 100 percent oversample of Black respondents. We also find that belief in systemic racism as a cause of police use of excessive force mediates much of the effects of the moral intuitions measures, except for the association between binding moral intuitions and positive feelings toward police, which is largely direct. Our results provide compelling evidence that moral intuitions play an important role in explaining American's divergent attitudes toward BLM and police.